Novel Genetic Variants of CDC25A Significantly Increase Risk of Spermatogenesis Arrest in Men from Bengali Population, India: A Cross-Sectional Study - Samudra Pal; Pranab Paladhi; Saurav Dutta; Ratna Chattopadhyay; Sujay Ghosh (Journal of Human Reproductive Sciences)
Background: Idiopathic azoospermia is one of the most common reasons for male infertility, but little is known about its genetic origins. The CDC25A gene, a meiotic core regulator, encodes a phosphatase that triggers the G1/S transition of meiosis. It dephosphorylates and activates CDK2, as well as enhances CDC2-cyclin E, CDK2-cyclin A and CDK1-cyclin B complex formation, which is crucial for chromosome condensation and progression of meiosis. Aim: The aim of this study was to identify individual variants of the CDC25A gene that make men susceptible to idiopathic azoospermia. Setting and Design: Genetic association study comparing the CDC25A gene in men with idiopathic azoospermia. Materials and Methods: The coding sequence of the entire CDC25A gene was sequenced in a population of azoospermic men. Recently discovered heterozygous mutations were assessed using in silico prediction tools to determine their possible pathogenicity. Statistical Analysis Used: Bioinformatics software such as SIFT, PolyPhen-2 and MutationTaster were applied to forecast the functional consequence of detected variants. Results: Novel heterozygous mutations were found in CDC25A. Variants present only in azoospermic men were evaluated for their pathogenicity, indicating their potential involvement in infertility. Conclusion: This work identifies new CDC25A gene variants that may be linked with idiopathic azoospermia. These discoveries add to the knowledge of the genetic aetiology of male infertility and could contribute to the development of future diagnostics and treatments.